Rocky Mountain vegetable gardening guide - Moore-Gough, Cheryl; Gough, Robert E. (Robert Edward) (TwoDot, 2016)
Rocky Mountain Vegetable Gardening Guide is the definitive guide to vegetable gardening in the five states that comprise the Rocky Mountain region. Professional horticulturist, Cheryl Moore-Gough, addresses the unique growing conditions and challenges of this region from how to select, grow, and harvest a host of vegetables that will succeed to offering tips for extending the season.